Impact of the National Lung Screening Trial (NLST) publication and Medicare Lung cancer screening payment on lung cancer incidence rates: An interrupted time series analysis. (March 2022) - Emmerick, Isabel Cristina Martins; Uy, Karl; Guiab, Keren; Powers, Maggie; Lou, Feiran; Lin, Poliana; Maxfield, Mark; Voland, Rick; Varlotto, John
Highlights: Medicare approval for CT-screening had a statistically significant effect on the diagnosis of early-stage lung cancer. Early-stage at diagnosis was associated with being female, white, insured, and from a household with income above median. Medicaid expansion (January-2014) contribute on improving ESLCD for those from households under the median income level. Abstract: Introduction: Explore the impact of the Lung Cancer Screening Trial (NLST-September-2011) and the Medicare approval for CT-screening (CT-LCS-AP-February-2015) on lung cancer incidence rates, mortality, and the percentage of early-stage lung cancer diagnosis (ESLCD-T1-T2N0M0). Methods: Retrospective interrupted time series analysis using SEER-18 database. All individuals with lung cancer (LC) diagnosis from 2006 to 2016 were included. The effect of NLST and CT-AP-2015 on the monthly percentage of early-stage ESLCD was the primary outcome, additionally LC incidence and mortality rates were calculated. The analysis was performed by age, sex, race, marital status, insurance status, and household income. Bivariate and multivariate models were used to identify predictors of ESLCD. Results: The study cohort was composed by 388, 207 individuals, 69 years old in average, 46.6 % female, and 81.1 % white. LC incidence and mortality rates declined from 2006 to 2016 without association with NLST-September-2011 and CT-LCS-AP-February-2015. The percentage of ESLCD increased over time for all groups. Overall rates of ESLCD started at 18 % in January-2006 and increased to 25 % by December-2016. The intervention NLST-2011 did not show an impact in the ESLCD while the CT-AP-2015 showed a significant impact in the ESLCD trend (p < 0.001). ESLCD was associated with female, white, insurance, and household incomes above median. Medicare expansion was a significant factor for insured group, married patients and those from households under the median income level. Conclusion: Medicare approval for CT screening was found to have a statistically significant effect on the diagnosis of early-stage lung cancer and neither NLST-September-2011 nor CT-AP-2015-February-2015 impacted the incidence nor mortality rates. Policy summary: To improve early-stage lung cancer diagnosis, it is vital to invest in health policies to increase Lung Cancer Screening implementation and to reduce disparities in access to diagnosis. Furthermore, policies that facilitate access to diagnosis and treatment are crucial to reduce lung cancer mortality.